Selection of peptide ligands for the antimucin core antibody C595 using phage display technology: definition of candidate epitopes for a cancer vaccine. Issue 3 (June 1995) - Laing, P; Tighe, P; Kwiatkowski, E; Milligan, J; Price, M; Sewell, H
Abstract : Aims —To further define the specificity of the antimucin core antibody C595 by fitting it with a family of hexapeptide ligands by immunoselection of filamentous bacteriophage from a gene III display library of approximately 6·4 × 10 7 random hexapeptides. Methods —Three rounds of immuno-selection were used to enrich for C595 binding phage. DNA sequencing revealed the hexapeptides expressed. Bacteriophage and corresponding synthetic hexapeptides were used in ELISA assay to determine binding affinities. Results —Twenty nine clones from this selected population were analysed. Seven contained the natural epitope RPAP, encoded by two different DNA sequences; 17/29 contained the motif RLPP. In all, 28/29 clones contained the motif RXXP and one clone (RVRPAP) contained the motif RXXP in two peptidic registers; 24/28 clones (6/8 DNA sequences) contained a hydrophobic residue (V or I) at position 1 relative to the RXXP motif. In addition the proximity of RXXP to glycine (position 5) suggests that this contributes in the natural epitope to antibody/antigen binding, which was not detected by chemical synthetic methods. One clone, KSKAGV, bears no obvious relationship to the natural epitope and therefore qualifies as a weakly binding mimotope. Conclusions —This approach has rapidly defined the specificity of this antibody in unprecedented detail, and provides a more comprehensive molecular basis for exploring the immune recognition of the MUC1 mucin by the C595 antibody. Importantly, the novel but related epitopes seen provide peptide specificities and a strategy which may prove useful in generating cancer vaccine candidates.